Clustering of noncommunicable disease risk factors among adults (18–69 years) in rural population, South-India. Issue 5 (September 2020) - Sarveswaran, Gokul; Kulothungan, Vaitheeswaran; Mathur, Prashant
Abstract: Background and aims: Non-communicable diseases (NCDs) and its risk factors are increasing worldwide and in India. Controlling the rise in risk factors at present is crucial to prevent NCD surge in future. Current study was conducted to estimate the burden of clustering of NCD risk factors among adult population (18–69 years) residing in selected villages of rural Bengaluru, Karnataka Methods: Population based screening for NCD risk factors were carried out among adults in rural Bengaluru during May to October 2019. NCD risk factors were screened using WHO STEPwise approach to chronic disease risk factor surveillance (STEPs) instrument and Integrated Disease Surveillance Project (IDSP) NCD risk factor tool. Presence of three or more risk factors in same individual was considered as presence of clustering of NCD risk factors. Additional analysis was done for clustering of NCD risk factors with different number of risk factors. Results: Prevalence of clustering of NCD risk factors in rural adult population was as follows; ≥2 risk factors 81.0%, ≥3 risk factors 56.3%, ≥4 risk factors 33.6%, ≥5 risk factors 14.5% and ≥6 risk factors 4.8%. The most common NCD risk factors were inadequate intake of fruits and vegetables (82.3%), physical inactivity (46.8%) and central obesity (46.4%). Clustering NCD risk factors were significantly associated with increased age, males and lower levels of education. Conclusions: High burden of clustering of risk factor indicates the need for health policies with integrated NCD risk factors prevention strategies than targeted approach. Awareness regarding the effect of clustering needs to be increased among the primary care physicians practising in rural areas. Highlights: In rural India, clustering of NCD risk factors is high and associated with increased age, males and lower education levels. Clustering of NCD risk factors does not vary across socioeconomic status in rural population. Primary prevention strategies need to be planned as an integrated approach to address the clustering of NCD risk factors. Primary care physicians practicing in rural areas need to be informed about the clustering effect in rural population.